MAGI-2 scaffold protein is critical for kidney barrier function - Balbas, Minna D. (National Academy of Sciences, 2014)
MAGUK Inverted 2 (MAGI-2) is a PTEN-interacting scaffold protein implicated in cancer on the basis of rare, recurrent genomic translocations and deletions in various tumors. In the renal glomerulus, MAGI-2 is exclusively expressed in podocytes, specialized cells forming part of the glomerular filter, where it interacts with the slit diaphragm protein nephrin. To further explore MAGI-2 function, we generated Magi-2–KO mice through homologous recombination by targeting an exon common to all three alternative splice variants. Magi-2 null mice presented with progressive proteinuria as early as 2 wk postnatally, which coincided with loss of nephrin expression in the glomeruli. Magi-2–null kidneys revealed diffuse podocyte foot process effacement and focal podocyte hypertrophy by 3 wk of age, as well as progressive podocyte loss. By 5.5 wk, coinciding with a near-complete loss of podocytes, Magi-2–null mice developed diffuse glomerular extracapillary epithelial cell proliferations, and died of renal failure by 3 mo of age. As confirmed by immunohistochemical analysis, the proliferative cell populations in glomerular lesions were exclusively composed of activated parietal epithelial cells (PECs). Our results reveal that MAGI-2 is required for the integrity of the kidney filter and podocyte survival. Moreover, we demonstrate that PECs can be activated to form glomerular lesions resembling a noninflammatory glomerulopathy with extensive extracapillary proliferation, sometimes resembling crescents, following rapid and severe podocyte loss.